2016
DOI: 10.1002/2016wr018783
|View full text |Cite
|
Sign up to set email alerts
|

The two‐phase flow IPTT method for measurement of nonwetting‐wetting liquid interfacial areas at higher nonwetting saturations in natural porous media

Abstract: Interfacial areas between nonwetting‐wetting (NW‐W) liquids in natural porous media were measured using a modified version of the interfacial partitioning tracer test (IPTT) method that employed simultaneous two‐phase flow conditions, which allowed measurement at NW saturations higher than trapped residual saturation. Measurements were conducted over a range of saturations for a well‐sorted quartz sand under three wetting scenarios of primary drainage (PD), secondary imbibition (SI), and secondary drainage (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 28 publications
5
17
0
Order By: Relevance
“…Larger X values produce larger interfacial areas for a given set of conditions, as a larger X represents a larger specific solid surface area due to greater magnitude of surface roughness. These results are consistent with prior experiment-based studies that have reported larger interfacial areas for media with greater surface roughness (Costanza & Brusseau, 2000;Costanza-Robinson & Brusseau, 2002;Peng & Brusseau, 2005;Brusseau et al, 2008Brusseau et al, , 2010Brusseau et al, , 2015Zhong et al, 2016).…”
Section: Sensitivity Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Larger X values produce larger interfacial areas for a given set of conditions, as a larger X represents a larger specific solid surface area due to greater magnitude of surface roughness. These results are consistent with prior experiment-based studies that have reported larger interfacial areas for media with greater surface roughness (Costanza & Brusseau, 2000;Costanza-Robinson & Brusseau, 2002;Peng & Brusseau, 2005;Brusseau et al, 2008Brusseau et al, , 2010Brusseau et al, , 2015Zhong et al, 2016).…”
Section: Sensitivity Analysissupporting
confidence: 92%
“…As expected, decreasing L m increases SA due to smaller grain size (and smaller pore size), which results in larger A nw for the full-range of saturations. These results are consistent with prior experiment-and model-based studies that have reported larger interfacial areas for media with smaller grain diameters (Cary, 1994;Anwar et al, 2000;Costanza & Brusseau, 2000;Costanza-Robinson & Brusseau, 2002;Cho & Annable, 2005;Dobson et al, 2006;Brusseau et al, 2008Brusseau et al, , 2009Brusseau et al, , 2010Costanza-Robinson et al, 2008;Zhong et al, 2016). The relative impact of surface roughness on A nw is greater for smaller L m , as illustrated by comparing the two sets of simulations for X = 1 and X = 50 for L m = 10 vs. 160 μm (Figure 6b).…”
Section: 1029/2019wr025876supporting
confidence: 90%
“…Additionally, Narter and Brusseau independently determined A max from interfacial partitioning tracer test measurements, and the resultant value (28 cm −1 ) was consistent with the XMT-based A max as well as the SSSA-NBET and GSSA. Zhong et al (2016) used a two-phase flow interfacial partitioning tracer test method to measure organic liquid-water interfacial areas for the same glass beads, and the A max (34 cm −1 ) is comparable to the values above. Finally, Lyu et al (2017) used the gas-absorption/chemical reaction method to measure air-water interfacial areas for the same glass beads.…”
Section: Benchmark Analysis Of Glass-bead Datamentioning
confidence: 99%
“…The significance of fluid‐fluid interfacial area for porous‐media systems has fomented the development and application of methods for its characterization and quantification. The methods available to measure fluid‐fluid interfacial area in natural porous media include mass‐balance tracer tests (Anwar, ; Anwar et al, ; Araujo et al, ; Karkare & Fort, ; Schaefer et al, ), aqueous and gas‐phase interfacial partitioning tracer tests (Brusseau et al, ; Cho & Annable, ; Costanza‐Robinson & Brusseau, ; Dobson et al, ; Jain et al, ; Kim et al, ; McDonald et al, ; Narter & Brusseau, ; Peng & Brusseau, ; Saripalli et al, ; Zhong et al, ), and pore‐scale imaging (Al‐Raoush, ; Al‐Raoush & Willson, ; Brusseau et al, ; Costanza‐Robinson et al, ; Culligan et al, ; Ghosh & Tick, ; McDonald et al, ; Porter et al, ; Prodanovic et al, ; Schnaar & Brusseau, ). Each method has associated limitations that can constrain their use.…”
Section: Introductionmentioning
confidence: 99%